ECONOMIC CRISIS THE LIMITS OF THE FLEXIBILITY OF CONTRACT LAW IN HUNGARY - Papp, Tekla (Comparative Law Review, 2014)
We analyse the influence and the ineffectivity of the economic crisis/business risk in the course of the dynamics of contract (from the contracting negotiations until the termination of contract) on the basis of the Hungarian Civil Code in force, and from the aspect of those contractual relations that cannot be found in the Hungarian Civil Code and finally, we look outside the current European regulations.